Running into trouble: COVID-19 in Japan during the Tokyo Olympics - Grout, L.; Summers, J.; Wilson, N.; Baker, M. (2021)
The 2020 Olympic Games were originally postponed due to the COVID-19 pandemic. The delayed event has now opened, with the opening ceremonies held on 23 July 2021 and competitions scheduled to take place through 9 August 2021. In this blog we look at the situation in Japan, as compared to NZ, and discuss lessons for nations considering hosting large events with international attendees during the COVID-19 pandemic. Here we consider the many public health implications of the decision to hold the Olympic and Paralympic Games in the middle of a global pandemic. These impacts include direct effects on the host country and city, effects on the attending athletes and staff themselves, and the indirect effects on global health and equity. Lessons from this event are also discussed. These concerns have also been highlighted in leading medical journals and by many commenters, particularly in Japan.